What price a welcome? Understanding structure agency in the delivery of respectful midwifery care in Uganda - Ackers, Louise; Webster, Hannah; Mugahi, Richard; Namiiro, Rachel (Emerald, 2018)
Purpose The purpose of this paper is to present the findings of research on mothers and midwives’ understanding of the concept of respectful care in the Ugandan public health settings. It focusses on one aspect of respect; namely communication that is perhaps least resource-dependent. The research found endemic levels of disrespect and tries to understand the reasons behind these organisational cultures and the role that governance could play in improving respect. Design/methodology/approach The study involved a combination of in-depth qualitative interviews with mothers and midwives together with focus groups with a cohort of midwives registered for a degree. Findings The findings highlight an alarming level of verbal abuse and poor communication that both deter women from attending public health facilities and, when they have to attend, reduces their willingness to disclose information about their health status. Respect is a major factor reducing the engagement of those women unable to afford private care, with health facilities in Uganda. Research limitations/implications Access to quality care provided by skilled birth attendants (midwives) is known to be the major factor preventing improvements in maternal mortality and morbidity in low income settings. Although communication lies at the agency end of the structure-agency continuum, important aspects of governance contribute to high levels of disrespect. Originality/value Whilst there is a lot of research on the concept of respectful care in high income settings applying this to the care environment in low resource settings is highly problematic. The findings presented here generate a more contextualised analysis generating important new insights which we hope will improve the quality of care in Uganda health facilities.